Inovasi Manajemen Pendidikan dalam Kegiatan Belajar Mengajar saat Masa Pandemi di Kabupaten Ngawi - Raden Willa Permatasari; Eka Purwanda (Jurnal Multidisiplin Madani, 2022)
Education is an important pillar for human resource development. Without education, there will be no next generation of intelligent, noble and tough people. This study aims to find out about the role of innovation in supporting teaching and learning activities through technological advances. This study used a qualitative descriptive approach by seeking data from the results of the study, conducting observations and interviews, where we took random samples from several elementary, middle, and high school levels in Ngawi Regency. The results of innovation research are useful in developing methods of teaching and learning activities that create new learning methods so that they are useful for improving learning management technology and providing continuous education for the community. Technological advances have an important role in teaching and learning activities during the pandemic, especially in Ngawi Regency in order to realize sustainable education that has an impact on people's lives.